3D Printing of polymer composites: A short review. Issue 2 (26th August 2019) - Singh, Sunpreet; Ramakrishna, Seeram; Berto, Filippo
Abstract: Composite or reinforced materials, especially in the class of polymers, are becoming prominent materials for the diversified range of engineering and scientific utilities because of their physical, chemical, mechanical, and structural excellences. Indeed, the main credit for the widespread acknowledgment of polymer matrix composites (PMCs) goes to the various types of natural and synthetic reinforcements, which resulted in good interfacial chemistries. However, the intrinsic challenges of traditional manufacturing technologies always presented restrictions in the development of application specific PMCs. Reportedly, with an evolution of three‐dimensional printing (3DP) technologies, the applications of PMCs have been transformed as these enabled the production of near‐net shapes with high degree of control over the design, reinforcements, and processing parametric while maintaining the waste associated at minimal level. However, the industrial benefits of 3DP technologies for still limited owing to the lack of awareness among the young professionals and industrialists. Moreover, the literature available in this regard is either too scattered making it tedious for the professionals to go through or limited to only fundamental concepts. Therefore, the concept of this review paper is to provide brief research‐based insights of different 3DP technologies (namely, fused deposition modeling, selective laser sintering, stereolithography, laminated object manufacturing, and inkjet printing), material systems, applications, and the future paradigms of research as a short and precise document.